miR-375 inhibits the proliferation of gastric cancer cells by repressing ERBB2 expression - SHEN, ZHI-YONG (D.A. Spandidos, 2014)
MicroRNAs (miRNAs) are small non-coding RNA molecules that regulate the expression of targeted genes in a post-transcriptional manner. Increasing evidence indicates that miRNAs play important roles in cancer pathogenesis, including apoptosis, proliferation and differentiation, as oncogenes or tumor suppressors. Previously, miR-375 was shown to be involved in human gastric cancer, however, the mechanism remains poorly understood. In the present study, miR-375 was shown to be downregulated in gastric cancer tissues, particularly human epidermal growth factor receptor 2 (ERBB2)-positive gastric cancer tissues. Identified by dual luciferase assays and western blot analysis, ERBB2 was demonstrated to be a target gene of miR-375. In addition, miR-375 overexpression suppressed the proliferation of human gastric cancer cells in vitro and the suppression effect was restored by ERBB2 overexpression. Thus, the results of the present study indicate that miR-375 is associated with human gastric carcinogenesis by targeting ERBB2. Therefore, miR-375 may be used as a potential clinical classification marker and therapeutic target for human gastric cancer.